Chemical instability promotes apparent electrochemical irreversibility: Studies on the electrode kinetics of the one electron reduction of the 2,6-diphenylpyrylium cation in acetonitrile solution - Streeter, I; Jenkinson, S; Fleet, G; Compton, R (2007)
Concentration profiles are obtained via numerical solution for the species involved in EC and EC2 mechanisms in a tubular flow cell. Voltammetric waves are simulated and the effect of the kinetic parameters on the waveshape is studied by considering the mass transport corrected Tafel slope. It is demonstrated that, when coupled to a follow up homogeneous step with sufficiently fast kinetics, a fast electron transfer may appear electrochemically irreversible in terms of its Tafel gradient. The electrochemical reduction of 2,6-diphenylpyrylium fluoroborate in acetonitrile solution is studied at a gold flow cell. Simulation of the recorded data permits us to infer a value of 1-2.5 × 10-3 cm s-1 for the standard electrochemical rate constant for the 2,6-diphenylpyrylium cation/radical couple. © 2006 Elsevier B.V. All rights reserved.